Landscape Restoran sebagai Daya Saing Pemasaran Wisata Kuliner Tradisional - Yanuar Reza Yulias; Kasno Pamungkas; Evi Novianti (Universitas Hamzanwadi, 2025)
The growth of the global tourism sector is closely tied to the increasing prominence of culinary tourism, which serves as both an economic driver and a medium for cultural preservation. In recent years, culinary destinations have actively promoted themselves through modern restaurants inspired by traditional architecture and regional cuisines. This trend reflects a structured commercial approach to sustaining cultural values while enhancing destination appeal. This study explores marketing strategies centered on traditional cultural attractions, including architectural heritage and local gastronomy that embody regional identity. A qualitative content analysis method was employed by examining promotional content and customer reviews published on Google Business Profiles. The units of analysis were selected purposively from culinary destinations known for their popularity and cultural representation. The findings reveal a new typology of digital marketing strategies rooted in local culture and storytelling. These strategies have proven effective in attracting tourists, increasing digital engagement, and strengthening destination competitiveness within the culinary tourism landscape. Furthermore, the study highlights the importance of collaboration among business owners, local communities, and digital platforms in fostering sustainable tourism growth. The research contributes to the development of culturally grounded tourism marketing models that can be adapted to various regional contexts across Indonesia. The study also provides practical insights for policymakers and tourism practitioners in designing integrated marketing strategies that align with sustainability principles.